Urban futures for central Canada : perspectives on forecasting urban growth and form - Bourne, Larry S. (University of Toronto Press, 1974)
Urban problems are now a dominant social issue: the essays in this volume consider the direction some of these problems may take in Central Canada. Three broad themes are discussed: forecasting (a spectrum of methodologies and urban forecasts); assessing the consequences of these forecasts at two levels (the growth of cities as an urban system and the growth and form of individual cities or urban regions); and assessing the role of changes in public policy. Specific topics include forecasting methodology in a spatial context, population and employment growth, migration, transportation, innovations, communication linkages, regional economic structure, economic fluctuations, the effects of public policy controls within a system of cities, land use and redevelopment, household mobility and social change, the spread of urban fields, and communities and neighbourhoods within cities.